Impact of Microfinance Operations on Market Women: Evidence from Madina Municipality, Ghana - Bismark, Okyere (IJRDO - Journal of Business Management, 2017)
The study investigated the impact of microfinance operations on the market women in Madina Municipal. Issues addressed includes, impact of the microfinance operations on the livelihood of market women, accessibility to loans, repaying of loan facility and challenges market women face in accessing loans from the microfinance institutions. The mixed method approach was adopted for the study. Questionnaire was distributed to the market women while the staff and management of selected microfinance institutions were interviewed. The study revealed that the operations of the microfinance had visible impact on the livelihood of the market women, their immediate and external families, access to loans was flexible as compared to the banks, but repayment rate among the market women was considerably not perfect. Besides, the study revealed that, the loans obtained were also put to good use by some of the market women and there were challenges associated with the activities of the microfinance. The study recommends among others that, there should be a platform for creating awareness for the market women to know the operations of the microfinance. The microfinance institutions should also adopt flexible procedures and methods that will encourage the market women to access more loans. The period of re-payment of loan facilities should also be flexible so that the market women can pay without difficulties. The microfinance institutions should also take a second look at the system of collateral security because it discourages most market women access to loan facility.